Two Sides of the Same Coin - Kelly, Spencer D.; Özyürek, Aslı; Maris, Eric (Psychological Science, 2010)
Gesture and speech are assumed to form an integrated system during language production. Based on this view, we propose the integrated-systems hypothesis, which explains two ways in which gesture and speech are integrated–through mutual and obligatory interactions–in language comprehension. Experiment 1 presented participants with action primes (e.g., someone chopping vegetables) and bimodal speech and gesture targets. Participants related primes to targets more quickly and accurately when they contained congruent information (speech: "chop"; gesture: chop) than when they contained incongruent information (speech: "chop"; gesture: twist). Moreover, the strength of the incongruence affected processing, with fewer errors for weak incongruities (speech: "chop"; gesture: cut) than for strong incongruities (speech: "chop"; gesture: twist). Crucial for the integrated-systems hypothesis, this influence was bidirectional. Experiment 2 demonstrated that gesture's influence on speech was obligatory. The results confirm the integrated-systems hypothesis and demonstrate that gesture and speech form an integrated system in language comprehension.